Investigation of large area sheet forming with laser shocking spot by spot. (15th December 2021) - Zhang, Xingquan; Niu, Wenwu; Zhang, Yan; Hu, Xingxing; Fang, Jinxiu; Zuo, Lisheng; Yin, Yuande; Shah, Syed Sohail Ahmad
Graphical abstract: Highlights: The cup with large area bottom can be formed with nine-spot laser shock in sequence. The different order of laser shocking can not change the final forming accuracy. An appropriate pressure of laser shock wave must be adopted in sheet shock forming. The forming accuracy rises with the raise of laser spot covering ratio within a threshold. Abstract: The paper presents a large-bottom cup formed by multiple-spot laser shocking. A 3D finite element model was developed with computational hardware and software resources to simulate the shape evolution process of cup manufactured by gradual-increasing-shot laser shocking along a specified path. A series of intermediate cups were fabricated correspondingly to verify the predicted results. The effect of key processes, such as impact order, imposed pressure of shock wave and the covering ratio of laser shocking spot, on the final geometric shape of formed cup was also investigated and analyzed. The results of numerical simulation and experiment show that small deformation induced by each single-spot shocking is gradually accumulated to larger deformation, and multiple-spot laser shocking can form the large conic cup well. The sheet forming precision is not affected by the order of laser shocking, but is seriously decreased by the improper pressure of imposed shock wave. When the covering ratio of laser shocking exceeds threshold value, sheet forming precision is not changed any more even if the covering ratio increases. In general, the multiple-spot laser shocking forming is a technology of sheet incremental forming, and it can enlarge greatly the scope of sheet forming with laser shocking.